O significado da iniciativa para a integração da infraestrutura regional Sul-Americana (IIRSA) no regionalismo Sul-Americano (2000-2012): um estudo sobre a iniciativa e a participação do Brasil - Honório, Karen dos Santos (2013)
This work aims to understand the meaning of the South America Iniciative for Integration of Regional Infrastructure (IIRSA), in the 21st regionalism in South America and also evaluate Brazil s participation on it. Our goal is the compreension of this object through a analytical description since its origins until the incorporation at the Conselho Sul-Americano de Infraestrutura e Planejamento (COSIPLAN) in 2009, seeking to understand how IIRSA worked and how countries and banks participated, focusing our analysis in Brazil. It was also our intention to go beyond the analysis of the IIRSA s project in 2000 and evaluate what this proccess can tell us about the regional integration in South America. We point that IIRSA did not forge any new arrangement regarding to the regional integration and instead, re-forced the tendency of a bilateral regionalism without supra-national charge. Each country participated and acted according to their own capacity, without a concerted action that could achieve , in terms of implementation, what were proposed